Internal Structure of the Central Garlock Fault Zone From Ridgecrest Aftershocks Recorded by Dense Linear Seismic Arrays. Issue 2 (14th January 2023) - Qiu, Hongrui; Chi, Benxin; Ben‐Zion, Yehuda
Abstract: We provide high‐resolution seismic imaging of the central Garlock fault using data recorded by two dense seismic arrays that cross the Ridgecrest rupture zone (B4) and the Garlock fault (A5). Analyses of fault zone head waves and P ‐wave delay times at array A5 show that the Garlock fault is a sharp bimaterial interface with P waves traveling ∼5% faster in the northern crustal block. The across‐fault velocity contrast agrees with regional tomography models and generates clear P ‐wave reflections in waveforms recorded by array B4. Kirchhoff migration of the reflected waves indicates a near‐vertical fault between 2 and 6 km depth. The P ‐wave delay times imply a ∼300‐m‐wide transition zone near the Garlock fault surface trace beneath array A5, offset to the side with faster velocities. The results provide important constraints for derivations of earthquake properties, simulations of ruptures and ground motion, and future imaging studies associated with the Garlock fault. Plain Language Summary: Along the northern edge of the Mojave Desert, the Garlock fault intersects the San Andreas fault and is the second largest (∼300 km long) fault in Southern California. It can host M  > 7 earthquakes that pose significant seismic hazard to densely populated communities. However, the subsurface structure of the Garlock fault is not well understood due to the sparse seismic network and lack of seismic activity nearby. The 2019 Ridgecrest earthquake sequence in the Eastern California Shear Zone led to a rapid deployment of several dense linear arrays with ∼100 m spacing and apertures of a few kilometers, which cross the Ridgecrest rupture zone and also the Garlock fault. The recorded seismic data is used here to illuminate the internal structure of the central Garlock fault. Analyses of P ‐wave delay times and waves refracted along and reflected by the fault interface indicate a near‐vertical Garlock fault that separates two distinctive crustal blocks with different wave speeds. The resolved high‐resolution fault zone image can have important implications for multiple studies associated with the Garlock fault. Key Points: We image the central Garlock fault using data of aftershocks of the 2019 Ridgecrest earthquake recorded by two dense linear arrays A P ‐wave velocity contrast across the fault (∼5% faster in the north) generates clear fault zone head and reflected waves Kirchhoff migration of P waves reflected by the fault indicates a near‐vertical interface with a sharp impedance contrast